The phytochemical and central nervous system investigation of aqueous and ethanolic extracts of leaves of Chromolaena odorata L. - Kamat, Nagesh; P Joshi, Madhusudan (Pharmacognosy Communications)
Introduction: The effect of the ethanolic and aqueous extracts of leaves of Chromolaena odorata L. on the central nervous system of rats was evaluated using a set of pharmacological screening methods. Materials and Methods: A single dose (100 mg/kg) of ethanolic and aqueous extract of leaves of Chromolaena odorata was administered to the rats orally to assess the pharmacological activity. Preliminary phytochemical testing preceded pharmacological screening tests for locomotion and spontaneous behavior conducted on the first, fourth and seventh day of administration. The Locomotor activity was evaluated using Rotamex and spontaneous behavior was studied by using Optovarimex. Results were compared using one-way analysis of variance (ANOVA) followed by Tukey- Kramer multiple comparison’s test. Results: On continuous administration of the extract, a dose dependent increase in spontaneous activity was observed in Optovarimex apparatus. There was an increase in distance travelled and a decrease in resting time in the Optovarimex instrument but no significant changes in ambulatory time and stereotypic time, while the DT of aqueous extract showed peak activity at 90 min on day 1. Conclusion: Preliminary phytochemical screening revealed that the C. odorata extract contains flavonoids, saponins, tannins, steroids and proteins. Our findings suggest that the extract has significant CNS stimulant activity. Furthermore, a marked increase in locomotor activity and an improvement in muscle coordination observed with the ethanolic leaf extract indicate that the above CNS activities may be attributed to the various phytoconstituents and antioxidants present in the leaf extract.
Keywords: Autotrack; Eupatorium odoratum; Locomotor; Optovarimex; CNS stimulant